The Symbolism and Socio-political Relevance of the Forts of Azad Jammu and Kashmir - Ashfaq Fazal (`, 2026)
The forts of Azad Jammu and Kashmir (AJK) reflect, perhaps more than anything else, the tangible remnants of history colliding with culture and unending socio-political issues within the region. In this article, I focus on the eclectic blend of architecture, history, and symbolism these forts possess whereby I examine their utilization as power over dominions or places of defiance and within the frameworks of community memory from medieval to modern times. With historical sources, fieldwork, observations, and comparative literature, this study focuses on AJK’s forts in relation to South Asia and post colonialism to emphasize their significance concerning regional identity formation as well as statehood narratives vis a vis governance over space along with contested heritage politics. The analysis demonstrates that these architectural structures are no longer static remnants of bygone eras but rather dynamic tools through which current day socio-political issues are interrogated in discourse about self-rule governance systems, conflict zones marked by persistent struggle alongside enduring resilience contrasting frameworks of turmoil versus tranquility which fuel debates on memory politics. Keywords: Symbolism, Socio-Political, Forts, Azad Jammu, Kashmir, Governance Systems